2014
DOI: 10.1016/j.jpsychires.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors in the depressed and suicide brain

Abstract: Abnormalities of the immune function in depression and suicide are based in part on the observation of increased levels of proinflammatory cytokines in the serum and postmortem brain of depressed and suicidal patients. We have examined if abnormalities of the innate immune receptors, known as Toll-like receptors (TLRs), in the brain are associated with depression and suicide, since the activation of these receptors results in production of cytokines. Of all the TLRs shown to be present in humans, TLR3 and TLR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 41 publications
1
96
0
3
Order By: Relevance
“…Our study found early exercise suppressed glial activity and proinflammatory cytokine expression as well as reducing anxiety‐like behavior. Anxiety‐associated proinflammatory cytokines released from immune cells, as a result of inflammation or stress, have abnormal serum levels in these patients (Pandey, Rizavi, Ren, Bhaumik, & Dwivedi, 2014; Toscano et al, 2016), and increased levels of cytokines contribute to the progress of depression and anxiety (Maldonado‐Bouchard et al, 2016). Our data showed exercise not only reduced the expression of inflammatory cytokines (IL‐6, TNF‐α) of MCAO rats significantly, but also reduced the expression of cell adhesion molecules (ICAM and VCAM), which mediated the leukocyte adhesion and infiltration in response to ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found early exercise suppressed glial activity and proinflammatory cytokine expression as well as reducing anxiety‐like behavior. Anxiety‐associated proinflammatory cytokines released from immune cells, as a result of inflammation or stress, have abnormal serum levels in these patients (Pandey, Rizavi, Ren, Bhaumik, & Dwivedi, 2014; Toscano et al, 2016), and increased levels of cytokines contribute to the progress of depression and anxiety (Maldonado‐Bouchard et al, 2016). Our data showed exercise not only reduced the expression of inflammatory cytokines (IL‐6, TNF‐α) of MCAO rats significantly, but also reduced the expression of cell adhesion molecules (ICAM and VCAM), which mediated the leukocyte adhesion and infiltration in response to ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood gene expression profiles revealed an overexpression of proinflammatory IL-6, IL-8, and type I IFN-induced signaling pathways [104,105,106,107]. Further, increased expression of a variety of innate immune genes and proteins, including IL-1β, IL-6, TNF-α, TLR3, and TLR4, has been found in postmortem brain samples from suicide victims that had depression [108,109]. …”
Section: Depressionmentioning
confidence: 99%
“…Although much of the attention of the literature has been focused on immunologic parameters in the peripheral blood, it should be noted that although the literature is not entirely consistent (Clark et al, 2016), increased activation of microglial cells as well as increased expression of inflammatory cytokines and Toll-like receptors have been described in postmortem brain samples of presumably depressed suicide victims (Steiner et al, 2008(Steiner et al, , 2011Pandey et al, 2012Pandey et al, , 2014Torres-Platas et al, 2014). Inconsistencies in the literature have been attributed to diagnostic considerations, use of medications, brain regions sampled, and small sample sizes.…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%